Politics of the Northwest Passage - Griffiths, Franklyn, 1935- (McGill-Queen's University Press, 1987)
Series of articles which summarize issues involved in Canada's claim to sovereignty over the Northwest Passage arranged in four parts: the setting; international arctic politics; Canadian arctic politics; conclusions.